THE ROLES OF TEACHER SUPPORTING GROUP FOR ELEMENTARY SCHOOL TEACHER PROFESSIONAL DEVELOPMENT - Syella Ardani; Syaid Hagung Buwono; Khairunnas Nur Putranto; Eka Puspita Dewi; Iin Inawati (PROJECT (Professional Journal of English Education), 2024)
One of the most important factors in enhancing a teacher's knowledge, attitudes, and abilities is professional development. With the implementation of a new curriculum by the government, Teacher Supporting Group role in enhancing teachers' professionalism is becoming more crucial. The purpose of this study is to determine roles of the English Teacher Supporting Group will support the professional development of teachers in Yogyakarta's elementary schools during the academic year 2022/2023. In the study, five English teachers from different accessible schools participated. In addition, the research was descriptive qualitative that uses questionnaires to gather information from the participants. Open-ended questionnaires were used as the method of data collection. The outcomes show that Teacher Supporting Group offers the Teacher Professional Development many advantages. First, through the activities conducted by Teacher Supporting Group, the teacher felt the significant contribution in helping them to gain Teacher Professional Development. Second, the improvement of educational quality is directly correlated with the professionalism of teachers. However, certain aspects need to be improved, such as including the research of the training requirements for teachers, the provision of long-term post-training monitoring, and the development of simple and efficient procedures for the administration of the school. Further research should concentrate on enhancing the aforementioned elements as a direction for future study.